Quantitative CT parameters correlate with lung function in chronic obstructive pulmonary disease: A systematic review and meta-analysis - Wang, Yan; Chai, Limin; Chen, Yuqian; Liu, Jin; Wang, Qingting; Zhang, Qianqian; Qiu, Yuanjie; Li, Danyang; Chen, Huan; Shen, Nirui; Shi, Xiangyu; Wang, Jian; et al. (Frontiers in Surgery, 2023)
Abstract Objective: The aim of the study was to analyze the correlation between quantitative computed tomography (CT) parameters and airflow obstruction in patients with COPD. Methods: PubMed, Embase, Cochrane and Web of Knowledge were searched by two investigators from inception to July 2022, using a combination of pertinent items to discover articles that investigated the relationship between CT measurements and lung function parameters in patients with COPD. Five reviewers independently evaluated the quality, extracted data, and evaluated bias. The correlation coefficient was calculated and heterogeneity was explored. The following CT measurements were extracted: percentage of lung attenuation area < -950 Hounsfield Units (HU), mean lung density, percentage of airway wall area, air trapping index, airway wall thickness. Two airflow obstruction parameters were extracted: forced expiratory volume in the first second as a percentage of prediction (FEV1%pred) and FEV1 divided by forced expiratory volume lung capacity. Results: A total of 141 studies (25,214 participants) were identified, 64 of which (6,341 participants) were suitable for meta-analysis. Results from our analysis demonstrated that there was a significant correlation between quantitative CT parameters and lung function. The absolute pooled correlation coefficients ranged from 0.26 (95% CI, 0.18 to 0.33) to 0.70(95% CI, 0.65 to 0.75) for inspiratory CT and 0.56 (95% CI, 0.51 to 0.60) to 0.74 (95% CI, 0.68 to 0.80) for expiratory CT. Conclusions: Results from this analysis demonstrated that quantitative CT parameters are significantly correlated with lung function in patients with COPD. With recent advances in chest CT, we can evaluate morphological features in the lungs that cannot be obtained by other clinical indices, such as pulmonary function tests. Therefore, CT can provide a quantitative method to advance the development and testing of new interventions and therapies for patients with COPD.